THE SPREAD OF ISLAM IN IJESALAND (1860 - 1968) (1988)
Islam, like any other religion in the society is an all-pervading phenomenon transforming individual lives in the society. Therefore, I commence this thesis by examining the ethno-historical and geographical background of Ijesaland. I also survey the traditional religious beliefs of the Ijesa as well as the religious and social milieu which were in existence when Islam was accepted there. The thesis is mainly on the introduction, the development and growth of Islam in Ijesaland for a period of about one hundred years (1860-1968). I discuss the advent, spread and the propagation of Islam in Ijesaland with emphasis on the various factors that contributed to its spread. These, in my opinion, include the various Muslim festivals and Ijesa Muslims’ enviable activities during the ‘Id-ul-Fitr and ‘Id—ul-Adha. I also discuss developments that brought about a setback for Islam in the area. These include the death of the first five pilgrims in 1910, the ‘gaga’ epidemic of 1917/18, the Babalola-Babatope revival of 1930 and Mooko-Mooka, (ability to read and write) introduced by the Christian Missionaries. I also examine the subsequent activities of the Muslims which led to further spreading of the faith among the people. As to the introduction of Islam in Ijesaland, my main claim is that unlike other parts of Yorubaland where non-indigenes introduced Islam, Islam was introduced and spread in Ijesaland by Ijesa people themselves through their commercial activities. Lastly, I discuss the difficulties involved in writing the history of Islam in Ijesaland. I also make suggestions on how to improve Muslims activities in Ijesaland.